Proceedings of the 24th International Conference on World Wide Web 2015
DOI: 10.1145/2740908.2741705
|View full text |Cite
|
Sign up to set email alerts
|

Tree Kernel-based Protein-Protein Interaction Extraction Considering both Modal Verb Phrases and Appositive Dependency Features

Abstract: Protein-protein interaction plays an important role in understanding biological processes. In order to resolve the parsing error resulted from modal verb phrases and the noise interference brought by appositive dependency, an improved tree kernel-based PPI extraction method is proposed in this paper. Both modal verbs and appositive dependency features are considered to define some relevant processing rules which can effectively optimize and expand the shortest dependency path between two proteins in the new me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…By the way, the Composite kernel version equipped with simplification rules improved F1-measure in almost 4 points compared to its previous version reported in [Miwa et al, 2009]. Moreover, although the Composite kernel had obtained the overall highest scores on the IEPA corpus, this kernel has high computation complexity and difficulty in implementation [Ma et al, 2015].…”
Section: Comparative Cross-validation Evaluationmentioning
confidence: 88%
See 4 more Smart Citations
“…By the way, the Composite kernel version equipped with simplification rules improved F1-measure in almost 4 points compared to its previous version reported in [Miwa et al, 2009]. Moreover, although the Composite kernel had obtained the overall highest scores on the IEPA corpus, this kernel has high computation complexity and difficulty in implementation [Ma et al, 2015].…”
Section: Comparative Cross-validation Evaluationmentioning
confidence: 88%
“…4 were taken from Quian and Zhou (2012). However, in [Ma et al, 2015], the authors reported an improvement of 1,2% percentage points in F1 over the SDP-CPT kernel results with their enhanced EOEP-CPT kernel. The main reason for such an improvement, according to the authors, is due to the fact that EOEP-CPT algorithm is more precise and concise than the SDP-CPT when both kernels uses the same version of the Stanford parser (v2.0.4).…”
Section: Comparative Cross-validation Evaluationmentioning
confidence: 96%
See 3 more Smart Citations